Hypothesis of quantum as a distributed self-organized computation by collective of particles - Pavel V. Kurakin (Discrete Dynamics in Nature and Society)
Previously we suggested an original interpretation of quantum mechanics. The interpretation supposes that quantum probability amplitudes are a manifestation of self-organization of nature at some deeper level of matter, performed in spatially and temporally distributed manner. Instead of formal description of the concept, the paper shows in detail how it works for basic quantum experiments.